International trade at the present stage - Deripaska, D.; Musatova, Inna; Мусатова, Інна Миколаївна; Мусатова, Инна Николаевна (ТДАТУ, 2018)
One of the oldest and most important forms of the international division of labor is international trade. In the framework of the international division of labor, there is a regular exchange of goods and services provided in accordance with the International Standards in force in the field of trade. This is any interstate exchange activity with goods, services and other results of human labor or elements of nature. It is a set of foreign trade of all countries of the world economy and creates the sphere of international trade and money relations
Keywords: world economy; international specialization; domestic market; international trade